Uit bet archief van AVRUG-Bulletin. ’Kongo. Een schoolvoorbeeld van kolonialisme ’. Een interview van 30 juni 1980 van W. Blondeel, V. Foutry en F. Van Mensel met Prof. Dr. A.A.J. Van Bilsen, RUG - Blondeel, William; Foutry, Vita; Van Mensel, Alfons (Afrika Focus, 2000)
This is a reprint, accompanied by a French translation, of an interview with Jef Van Bilsen (1913-1996), the former Belgian adviser to the first Congolese President, Joseph Kasavubu. The interview was conducted when Van Bilsen was a professor at the University of Ghent. Van Bilsen is questioned about his ’Thirty Years Plan’ to prepare the Belgian Congo for independence. The plan, published in 1955, provoked strong criticism in the Belgian political and academic establishment because at that time decolonisation was not accepted on the political agenda, at least not within thirty years. Van Bilsen describes the narrow minded and extreme paternalistic vision of the Belgian colonial administration and the awakening of Congolese nationalism. The consequence of this cramped policy is that in 1960 Belgium grants independence to the Congo in a reaction of panic and in a completely unprepared way. Furthermore, Van Bilsen relates, as a privileged witness, the disastrous outcome of foreign interference in the struggle between President Kasavubu, Prime Minister Lumumba and the Katangese secessionist, Tshombe. He cites his statement to Tshombe that Lumumba could not be seen as a communist and reports how he advocated a compromise between the three opponents.